The Industrial Attachment Programme - History, Benefits, Challenges and its Adoption in Zimbabwe: A Review - Dondofema, J.; Mwenje, J.; Musemwa, L. (Asian Journal of Education and Training, 2020)
Tertiary education institutions are seen to be increasingly incorporating industrial attachment as a training methodology. This is happening with the private and public sectors. It is of the view that during the industrial attachment phase, the student is accorded an opportunity to marry theory learnt in the classroom with the real field of work. Among other training methodologies, industrial attachment was found to be key with respect to professional etiquette doing extremely well in combination with other methodologies. This review paper covers history of industrial attachment, benefits derived from the Industrial Attachment Programme (IAP) by the students, tertiary education institutions, host organizations and the industry at large. The paper also highlights challenges faced by key players in the circle of the IAP. The review will assist in improving the way institutions of higher learning, government departments and host organizations conduct the programme to enhance the multiplier positive effects and minimize the costs of the IAP.